Association of oxidative balance score with the risk of all-cause and CVD mortality in younger US adults with diabetes - Chang Liu; Guoan Xiang; Dan Liang; Xuanbo Zhao; Kun Xiao; Lixin Xie (Scientific Reports)
Abstract Oxidative balance score (OBS) is a composite measures that assess the balance between pro-oxidant and antioxidant factors in an individual’s diet and lifestyle, with higher scores indicating greater antioxidant exposure. Despite its potential significance, there is a limited body of research exploring the relationship between OBS and all-cause and cardiovascular disease (CVD) mortality specifically in younger patients with diabetes. We aimed to investigate the possible relationship between OBS and all-cause and CVD mortality in younger patients with diabetes. Data for this study were obtained from the 2003–2018 NHANES. This study enrolled 3501 participants. The endpoints were all-cause and CVD mortality, determined by the National Death Index (NDI). OBS, which consists of 16 dietary factors and 4 lifestyle factors, is categorized into pro-oxidants and antioxidants. The OBS was categorized into four quartiles (Q1-Q4). We used multivariable Cox proportional hazards regression models to examine the association between continuous and quartile measures of OBS, lifestyle OBS (lifestyle antioxidants such as physical activity, etc., and lifestyle pro-oxidants such as alcohol, smoking, etc.), and dietary OBS (dietary antioxidants such as fiber, β-carotene, riboflavin, etc., and dietary pro-oxidants, such as total fat, etc.) with all-cause and CVD mortality. Additionally, we explored restricted cubic spline (RCS) analysis and also performed subgroup analyses and interaction tests. The occurrence of 409 all-cause deaths (11.7%) and 108 CVD-related deaths (3.1%) was recorded during the follow-up period. Our results found that OBS, lifestyle OBS, and dietary OBS were negatively associated with patients’ all-cause and CVD mortality. The RCS analysis further validated the association of a linear negative correlation between OBS and all-cause and CVD mortality. The results of our subgroup analyses revealed that the negative association between OBS and CVD mortality may be influenced by alcohol use. In conclusion, results from a nationally representative study of younger American patients with diabetes suggest a negative association between OBS, lifestyle OBS, and dietary OBS and all-cause and CVD mortality. Antioxidant-rich diets and lifestyle improvements are essential for reducing all-cause and CVD mortality in patients.